The Main Character's Jealousy as Seen in Gillian Flynn's Gone Girl: A Psychological Approach - Ganesh Yogi Prabowo; Astry Fajria (Ahmad Dahlan Journal of English Studies, 2021)
Jealousy is part of human's psychological condition. Similarly, Gillian Flynn employed the topic brilliantly in one of her works, Gone Girl. The present study entitled "The Main Character's Jealousy as Seen in Gillian Flynn's Gone Girl" aimed to identify the main character's personality and to describe the causes and impacts of her jealousy. It belongs to library research, with Gillian Flynn's novel as the subject and the aspects of jealousy the object. Since it is about the human psyche, a psychological approach was employed. Further, the theories of jealousy were used to analyze the data and to answer the research questions. The analysis resulted in several findings. First, Amy Dunne, the main character, was found to be a brilliant and cunning person. Her personality, triggered by jealousy, manifests in her actions throughout the story. Second, Amy Dunne is extremely jealous of her husband. She finds out that Nick, her husband, has an affair with another woman, and the feeling leads to several incidents. Amy disappears, fakes various crime that leads the public to hate her husband, and finally returns home. Amy also kills a man to cover her lies; all were done without anyone's suspicion. It is recommended that the next researchers explore the characters of the story more profoundly or employ the work as one alternative material in ELT class.